GE_GERICHTE C/12644/2017 vom 6. März 2018 - GE Cour de justice (2018)
DROIT DE LA FAMILLE ; ENFANT ; MINORITÉ(ÂGE) ; OBLIGATION D'ENTRETIEN ; FRAIS D'ENTRETIEN ; CALCUL ; MINIMUM VITAL ; REVENU | CC.176.al3; CC.285.al1